Internal duplication in human alpha 1 and beta 1 interferons. - Erickson, B W (1984)
Metric analysis of the nucleotide sequence of the intron-free human interferon beta 1 (IFN-beta 1) gene by using the Sellers TT algorithm revealed that this gene contains two major repeated segments, which span the entire coding region. These repeats are each approximately 300 nucleotides in length and have 45% identical aligned nucleotides (common bases). When these metrically aligned DNA repeats were translated into amino acids, 9 (19%) of the 47 in-phase amino acid residues were identical (common acids). This internal duplication was also apparent on visual inspection of the amino acid sequence of IFN-beta 1. In addition, metric analysis of the nucleotide sequence of the intron-free IFN-alpha 1 gene showed that this gene also contains two repeats, each approximately 300 nucleotides long, having 47% common bases and 19% common acids. Since the IFN-alpha 1 and -beta 1 genes are known to be related (by the present metric analysis they contain 53% common bases and 45% common acids), a consensus DNA sequence was derived from all four of these repeats. Manual alignment of the separate metric alignments corresponding to the two halves of the IFN-alpha 1 and -beta 1 genes provided a composite alignment with 58% of the alignment positions having the same nucleotide in at least three of the four repeats. When this composite nucleotide alignment was translated to define a composite alignment of the four protein segments, 10 (31%) of the 32 in-phase amino acid residues contained the same amino acid in at least three of the four segments. These sequences relationships provide insight into the origin of the IFN-alpha 1 and -beta 1 genes and furnish an additional basis for comparing them with other related genes.